Factors affecting the prey preferences of jackals (Canidae) - Hayward, MW; Porter, L; Lanszki, J; Kamler, JF; Beck, JM; Kerley, GIH; Macdonald, DW; Montgomery, RA; Parker, DM; Scott, DM; O’Brien, J; Yarnell, RW (Elsevier, 2017)
Prey selection by carnivores can be affected by top-down and bottom-up factors. For example, large carnivores may facilitate food resources for mesocarnivores by providing carcasses to scavenge, however mesocarnivores may hunt large prey themselves, and their diets might be affected by prey size and behaviour. We reviewed jackal diet studies and determined how the presence of large carnivores and various bottom-up factors affected jackal prey selection. We found 20 studies of black-backed jackals (Canis mesomelas) from 43 different times or places, and 13 studies of Eurasian golden jackals (Canis aureus) from 23 different times or places reporting on 3900 and 2440 dietary records (i.e. scats or stomach contents), respectively. Black-backed jackals significantly preferred small (<30 kg) ungulate species that hide their young (duiker Sylvicapra grimmia, bushbuck Tragelaphus scriptus and springbok Antidorcas marsupialis), and avoided large (>120 kg) hider species and follower species of any body size. They had a preferred and accessible prey weight range of 14–26 kg, and a predator to ideal prey mass ratio of 1:3.1. Eurasian golden jackal significantly prefer to prey on brown hare (Lepus europaeus; 4 kg), yielding a predator to preferred prey mass ratio of 1:0.6, and a preferred and accessible prey weight range of 0–4 kg and 0–15 kg, respectively. Prey preferences of jackals differed significantly in the presence of apex predators, but it was not entirely due to carrion availability of larger prey species. Our results show that jackal diets are affected by both top-down and bottom-up factors, because apex predators as well as prey size and birthing behaviour affected prey preferences of jackals. A better understanding of the factors affecting jackal prey preferences, as presented here, could lead to greater acceptance of mesocarnivores and reduced human-wildlife conflict.